Drgania Fundamentów w Czasie Rozruchu Silników Wirnikowych - Bogusz, W. (Engineering Transactions, 1958)
A method proposed for the solution of an important case of elastic vibration with varying frequency of the vibration exciting force. This method is based on integral equations for functions of the complex variable. The vibration of the foundation during the process of starting a turbine is reduced to that of a system of one degree of freedom. The method described is used for two different cases of starting a turbine.